Analysis Of Factors Affecting The Quality Of Development Of Regional Income And Expenditure Budgets, Deli Serdang Regency - Irna Triannur Lubis; Adekasna Rosadi Pohan (Enrichment : Journal of Management, 2022)
This study aims to determine and analyze the effect of Information Technology Utilization and Human Resource Competence on the Quality of Regional Revenue and Expenditure Budgeting. This type of research is causal and the object of this research is Deli Serdang Regency. The data used is primary data obtained from a questionnaire with a total sample of 62 respondents. Research data Using a quantitative approach and data analysis using a simple regression analysis model. The results of the study indicate that the use of Information Technology and Human Resource Competence has a partial effect on the quality of the preparation of the Regional Revenue and Expenditure Budget.